The Impact of the Marketing Mix on Consumer Purchasing Decisions at Dapoer Uni Elvy Catering in Bandung - Raihan, Muhammad; Nandang, Nandang; Yusuf, Ismail (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the impact of the marketing mix on consumer purchasing decisions at Dapoer Uni Elvy Catering, located in Bandung. In recent years, the company has experienced a significant decline in the number of orders, which is suspected to be due to weak marketing strategies and price competition from competitors. This research applies a quantitative approach using a descriptive method. Purchasing decision is the dependent variable, while product, price, and promotion are the independent factors. A questionnaire was distributed to 108 active consumers over the past year. This study can help SMEs develop more effective marketing strategies to compete and retain customers.